Electrocardiograph compression based on sifting process of empirical mode decomposition. Issue 9 (4th April 2016) - Zhao, Chaojun; Chen, Zhijian; Meng, Jianyi; Xiang, Xiaoyan
Abstract : A new empirical mode decomposition (EMD)‐based electrocardiograph (ECG) compressor is presented. Utilising the sifting process in EMD, the spline fitting function of the successive mean extrema together with the first intrinsic mode functions can perfectly reconstruct the ECG signal, the proposed method using the mean extrema for the compression. With optimal selection of the mean extrema and dead zone quantisation, and the application of run length coding and Huffman coding for further compression, the experimental results regarding several records of the MIT‐BIH arrhythmia database shows that the proposed methods have a better compression results than recently developed ECG compressors.